Slippery for scaling resistance in membrane distillation: A novel porous micropillared superhydrophobic surface. (15th May 2019) - Xiao, Zechun; Zheng, Rui; Liu, Yongjie; He, Hailong; Yuan, Xiaofei; Ji, Yunhui; Li, Dongdong; Yin, Huabing; Zhang, Yuebiao; Li, Xue-Mei; He, Tao
Abstract: Scaling in membrane distillation (MD) is a key issue in desalination of concentrated saline water, where the interface property between the membrane and the feed become critical. In this paper, a slippery mechanism was explored as an innovative concept to understand the scaling behavior in membrane distillation for a soluble salt, NaCl. The investigation was based on a novel design of a superhydrophobic polyvinylidene fluoride (PVDF) membrane with micro-pillar arrays (MP-PVDF) using a micromolding phase separation (μPS) method. The membrane showed a contact angle of 166.0 ± 2.3° and the sliding angle of 15.8 ± 3.3°. After CF4 plasma treatment, the resultant membrane (CF4 -MP-PVDF) showed a reduced sliding angle of 3.0°. In direct contact membrane distillation (DCMD), the CF4 -MP-PVDF membrane illustrated excellent anti-scaling in concentrating saturated NaCl feed. Characterization of the used membranes showed that aggregation of NaCl crystals occurred on the control PVDF and MP-PVDF membranes, but not on the CF4 -MP-PVDF membrane. To understand this phenomenon, a "slippery" theory was introduced and correlated the sliding angle to the slippery surface of CF4 -MP-PVDF and its anti-scaling property. This work proposed a well-defined physical and theoretical platform for investigating scaling problems in membrane distillation and beyond. Graphical abstract: Image 1 Highlights: MicroMolding phase separation (μPS) was utilized to prepare pillared hydrophobic membranes. Porous micropillars PVDF surface appeared superhydrophobic. CF4 plasma modification turned the surface from superhydrophobic to slippery. Slippery surface showed significant resistance to scaling in treating saturated NaCl solutions by membrane distillation.